Misi Gereja Dalam Realitas Sosial Indonesia Masa Kini - Kalis Stevanus; Yunianto Yunianto (STTI Harvest Semarang, 2021)
In general, the problem of mission today is related to a one-sided emphasis on one side. One emphasizes and maintains the context of the humanitarian field with all its problems and challenges so that it tends to ignore the text. While others are fixated on the text and ignore the context. It is undeniable that the mission paradigm will influence and determine its missionary practice. This paper is intended to contribute theoretically about the importance of reconstructing the Church's mission paradigm that is relevant to the context of today's Indonesia, and practically the churches in Indonesia can implement an applicable form of mission by taking part in alleviating the concrete problems faced. by the community according to the capabilities of the church members. By using a qualitative approach, namely a literature study, the author will describe descriptively about the foundation of Christian mission and the urgency of conducting a review or updating of the understanding and practice of its mission in the current concrete situation. It was concluded that the mission of the church must still be carried out but in its implementation it must pay attention to the social situation in the community. Because the mission of the church without paying attention to the context of its recipients will find difficulties and even failures in carrying out God's will as the light and salt of the world. This means that the strategy or technique of the church's mission must be implemented according to the current context in which the church is present.